Influence of playing surface on match injury risk in men's professional rugby union in England (2013-2019) - Robertson, C. M.; Williams, S.; West, S. W.; Starling, L.; Kemp, S.; Cross, M.; Stokes, K. A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The use of artificial playing surfaces in professional rugby union is growing, but their effect on the injury risk profile remains unclear. The aim of this study was to examine the effect of playing surface on match injury risk in men's professional rugby in England. Six seasons of injury data (2013/14-2018/19) were collected from 15 professional English, men's rugby teams participating in domestic and European competition. The incidence, severity, and burden of match injuries were compared across playing surfaces. The dataset included 3351 injuries from a combined European and domestic data set (separated in to 2 categories; artificial and natural/hybrid surfaces) and 2675 injuries from a domestic only dataset (separated into 3 categories; artificial, hybrid, and natural surfaces). There were no differences in incidence rates between surface types on combined European and domestic match data, but injury burden was significantly greater on artificial (3082 days/1000 h, 95% CI 2847-3337) in comparison with natural/hybrid surfaces (2364 days/1000 h, 95% CI 2277-2454, p < 0.001). These differences were primarily driven by a significantly greater mean severity of hip/groin, and foot/toe injuries on artificial surfaces. This is the largest study to date to examine the relationship between surface type and injury risk in rugby union. The average severity and burden of injuries sustained on artificial surfaces was significantly greater compared with those sustained on hybrid/natural grass surfaces. This study can inform those involved in selection of surface for elite sport, weighing up the positive and negative elements of the varying surface types.